PENGARUH KUALITAS PELAYANAN PUBLIK TERHADAP KEPUASAN PELANGGAN DI PERUSAHAAN DAERAH AIR MINUM (PDAM) TIRTA PATRIOT KOTA BEKASI - Rina Susanti Hartono; Siti Nuraini; Pria Sanubari (Governance, 2023)
This research titled The Effect of Public Service Quality Towards Costumer Satisfaction in PDAM Tirta Patriot Kota Bekasi. Based on the problem about costumer satisfaction about this matter with service quality that has not optimal yet. The purpose of this research was to know tangible, responsiveness, reliability, assurance and emphaty effects towards satisfaction of PDAM’s costumer in Kota Bekasi. This research used survey method with the population is all costumer of PDAM Tirta Patriot Kota Bekasi with total sample 395 costumers. Data collection technique that used in this research was random sampling. Analysis technique using correlation coefficient technique, with test T and test F using SPSS software. The result of this research shows that physical evidence (tangible) has positive and significance effects towards satisfaction of PDAM Tirta Patriot Kota Bekasi costumers. Responsiveness has positive and significance effects towards satisfaction of PDAM Tirta Patriot Kota Bekasi costumers. Reliability has positive and significance effects towards satisfaction of PDAM Tirta Patriot Kota Bekasi costumers. Assurance has positive and significance effects towards satisfaction of PDAM Tirta Patriot Kota Bekasi costumers. Emphaty has positive and significance effects towards satisfaction of PDAM Tirta Patriot Kota Bekasi costumers.